A design evaluation of the Kingdom Hall in the Philippine branch office of Jehova's Witnesses - Alcantara, Jan Wray A.; Faustino, Johanna Victoria Acab (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT This case study discusses the design elements present in the Kingdom Hall of the Philippine Branch Office of the Jehovah?s Witnesses. As a worship center, the Kingdom Hall must satisfy its role as a religious center, yet devoid of any physical religious manifestations. As such, this study aimed to find out if the existing interior of the Kingdom Hall meets the expectations of its members. Using the Theory of Sense of Place as a guiding framework for research, the study, through various methods of data gathering, assessed and evaluated the facility that the members use for their worship using the following design criteria and characteristics: space planning and arrangement, acoustics, lighting, ventilation, furniture, safety and security, user-friendliness, universality, aesthetics, and comfort. Through purposive sampling, 50 members of the Jehovah?s Witness congregation in the Philippine Branch at Roosevelt, Quezon City, were chosen as respondents of the study, and 5 members with spiritual privileges were interviewed. Results revealed that the design of the Kingdom Hall is based on the physical and social needs of its members. Among all the design characteristics, space planning and arrangement, specifically circulation, needed substantial improvement. While the Respondents view the space as generally comfortable, meeting all the design characteristics in various activities within the area may further improve their sense of place in the interior setting. In order for their worship to be more effective, the interior of the Kingdom Hall must provide a stress-free environment that promotes their spiritual focus and satisfaction.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Church buildings -- Designs and plans -- Philippines -- Quezon City; Kingdom Hall of Jehovah's Witnesses -- Philippines -- Quezon City